Covid, Crisis, Care, and Change? International Gender Perspectives on Re/Production, State and Feminist Transitions - Kupfer, Antonia; Stutz, Constanze (Verlag Barbara Budrich, 2022)
Die Covid-19-Krise hat bereits bestehende soziale Ungleichheiten in verschiedenen Bereichen verschärft. Die Autor*innen untersuchen, wie grundlegend und nachhaltig die sozialen Veränderungen im Zuge der Corona-Pandemie auf den gesellschaftlichen Ebenen Arbeit, Sorgearbeit und staatliche Regulierung in ihren geschlechtsspezifischen Dimensionen sind.; The Covid-19 crisis has intensified already existing social inequalities in different spheres. The authors examine how fundamental and sustainable the social changes over the course of the corona pandemic are at the social levels of labour, care work and state regulation in their gender dimensions.